Mapping Brand Equity and Service Quality Perceptions : A Comparative Study of National Private Banks in Indonesia - Heriana, Ferra; Sibarani, Mentiana; Silitonga, Roland Y.H.; Heryanto, Dhany (Journal of Management Studies and Development, 2023)
This study aims to create a map of brand equity and service quality perceptions of Bank C relative to four other banks in Indonesia, namely Bank KBMI Category 3. Customer perception maps were constructed by asking customers to provide overall similarity ratings for Brand Equity and Service Quality pairs on a metric scale. The study included Bank A, Bank B, Bank C, Bank D, and Bank E customers in Indonesia. One hundred eight respondents were sampled using the Exploratory Factor Analysis (EFA) method, which groups many variables into several factors with similar characteristics. Additionally, the Multidimensional Scaling (MDS) method was used, a data analysis technique used to explore the data structure based on similarities or dissimilarities. Based on the analysis results, it was found that according to the perceptions of Bank C customers, the bank scored low in the Reliability factor. At the same time, Bank B had the lowest scores in Brand Loyalty and Brand Awareness factors. This indicates that the strengths of both banks lie in these factors. Subsequently, Bank A, Bank E, and Bank D followed in sequential order.